2017
DOI: 10.1089/scd.2017.0068
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Dental Pulp-Derived Stem Cells or Differentiated Neuronal Cells from Human Dental Pulp-Derived Stem Cells Identically Enhances Regeneration of the Injured Peripheral Nerve

Abstract: Human dental mesenchymal stem cells isolated from the dental follicle, pulp, and root apical papilla of extracted wisdom teeth have been known to exhibit successful and potent neurogenic differentiation capacity. In particular, human dental pulp-derived stem cells (hDPSCs) stand out as the most prominent source for in vitro neuronal differentiation. In this study, to evaluate the in vivo peripheral nerve regeneration potential of hDPSCs and differentiated neuronal cells from DPSCs (DF-DPSCs), a total of 1 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 30 publications
0
56
0
2
Order By: Relevance
“…In light of these observations, the present study demonstrated that long-term preserved dental pulp tissues stored under the newly developed tissue cryopreservation protocol could safely conserve multipotent stem cells, as shown by the same MSC characteristics as those derived from fresh dental pulp tissues. Both hDPSCs-fresh and hDPSCs-cryo showed the same cell morphology, proliferation rates, cell-surface markers expression, and in vitro differentiation potential as the mesenchymal lineage [15,16,24]. In accordance with previous reports, hDPSCs-cryo used in this study retained their MSC characteristics and were shown to positively express early transcription factors (Nanog, Oct4, Sox2) and MSC markers (CD29, CD73, CD90), and successfully differentiate into the mesenchymal lineage (osteocytes, adipocytes, and chondrocytes).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In light of these observations, the present study demonstrated that long-term preserved dental pulp tissues stored under the newly developed tissue cryopreservation protocol could safely conserve multipotent stem cells, as shown by the same MSC characteristics as those derived from fresh dental pulp tissues. Both hDPSCs-fresh and hDPSCs-cryo showed the same cell morphology, proliferation rates, cell-surface markers expression, and in vitro differentiation potential as the mesenchymal lineage [15,16,24]. In accordance with previous reports, hDPSCs-cryo used in this study retained their MSC characteristics and were shown to positively express early transcription factors (Nanog, Oct4, Sox2) and MSC markers (CD29, CD73, CD90), and successfully differentiate into the mesenchymal lineage (osteocytes, adipocytes, and chondrocytes).…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the scale of motor nerve regeneration in vivo, DF-chN were transplanted into experimental rats with sciatic nerve defects using collagen tubulization and a fibrin glue scaffold. In this study, biodegradable bovine collagen dura mater (Lyoplant ® , Aesculap, Melsungen, Germany) was contoured and sutured to create the tube and bridging for the resected nerve ends, as per previous studies [11,16]. This tubulization provided a mechanical support system for regenerating and remodeling nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations